Laparoscopic Colorectal Resection in Octogenarian Patients: Is it Safe? A Systematic Review and Meta-Analysis. Issue 42 (October 2015) - Xie, Minghao; Qin, Huabo; Luo, Qianxin; He, Xiaosheng; Lan, Ping; Lian, Lei
Abstract : Abstract: The population older than 80 years has been increasing. A significant proportion of colorectal diseases that require colorectal resection occur in very elderly patients. However, the benefits of laparoscopy remain controversial in octogenarians. A systematic review and meta-analysis of observational study was performed to compare clinical outcomes between laparoscopic versus open colorectal resection in octogenarians. The PubMed, EMBASE, Ovid, Web of Science, and Cochrane databases from the years 1990 to 2015 were searched for studies that compare surgical outcomes between laparoscopic and open colorectal resection in octogenarians (≥80 years old). Seven eligible studies including 528 laparoscopic and 484 open colorectal resections were identified. Laparoscopic approach was associated with lower rate of mortality (odds ratio [OR] 0.48, P = 0.03), overall complications (OR 0.54, P < 0.001), and prolonged ileus (OR 0.56, P = 0.009), quicker bowel function return (standardized mean difference [SMD] −0.50, P < 0.001), and shorter length of hospital stay (SMD −0.47, P = 0.007). No differences were found in anastomotic leak (OR 1.16, P = 0.72), respiratory complication (OR 0.60, P = 0.07), and reoperation (OR 0.85, P = 0.69). Laparoscopic colorectal resection is as safe as open approach, and the short-term outcomes appear to be more favorable in octogenarians.